Green Consumerism: Determinants Of Green Product Purchase Decisions At Kedai Pustaka Coffee Shop, Bangkalan Regency, Madura Island - Afriani, Ferina; Kurniyanto, Ifan Rizky; Hasan, Fuad; Suprapti, Isdiana (Universitas Teuku Umar, 2025)
The emergence of coffee shops in various corners of the city can impact the environment, especially regarding waste production. More and more consumers are environmentally conscious, demanding business actors to develop environmentally friendly products. Like the Kedai Pustaka coffee shop, it is one of the coffee shops in Bangkalan Regency that has implemented green products. Green products themselves have a more minor impact on the environment overall. Due to implementing this policy, a decrease in sales turnover is possible, which will affect business sustainability. This study aims to discover the factors influencing consumers' purchase of green products at Kedai Pustaka. The determination of the research location was purposive, so the Kedai Pustaka was chosen as the research object. Data was collected for 43 respondents with an axial sampling technique and then analyzed using the Smart-PLS application through the SEM-PLS approach. It was found that environmental knowledge influenced attitude, and environmental attitude significantly affected the purchase decision of green products. Kedai Pustaka is expected to grow and improve knowledge and attitude toward caring for the environment from the consumer side